Analisisi Strategi Pendidikan dalam Membentuk Karakter Peserta Didik di MTs Nahdhatul Ulama Sibuhuan - Basaruddin Hsb (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas (STIT PL) Gunung Tua, 2025)
Character education at Madrasah Tsanawiyah Swasta Nahdhatul Ulama Sibuhuan differs from that of other Islamic junior high schools. Since its establishment, the school has consistently implemented a daily seven-minute religious lecture (kultum) during the morning assembly and, more recently, has introduced the weekly recitation of Surah Yasin every Friday. These distinctive practices motivated the researcher to conduct this study at the institution. This study aims to identify the strategies used to develop character education and to examine the supporting and inhibiting factors encountered by teachers in implementing character education at MTs Nahdhatul Ulama Sibuhuan. The study employed a qualitative field research approach with a descriptive design. Data were collected through observation, interviews, and documentation. The findings indicate that teachers develop students' character by instilling religious values, honesty, discipline, nationalism, and appreciation for achievement. The supporting factors include teachers' personal approach to students, special attention given to individual learners, effective coordination among teachers, and the establishment of a school culture that promotes noble moral values. Meanwhile, the inhibiting factors include students' lack of self-awareness, limited parental support regarding disciplinary measures implemented by school supervisors, and parental interference in the school's character-building and educational processes. To address these challenges, the school emphasizes strong commitment and motivation among teachers and supervisors, mutual understanding among school supervisors, parents, and students regarding the implementation of school regulations, continuous improvement of the supervisors' human resources, strengthened collaboration among teachers, and teachers serving as exemplary role models for students.